A sulfonic acid group functionalized Ti4O7 material, a preparation method thereof and application of the material in uranium extraction from high-fluorine wastewater

The selective separation of uranyl ions in a high-fluoride environment was solved by using sulfonic acid-functionalized Ti4O7 materials, achieving efficient electrochemical uranium extraction. This overcomes the selectivity bottleneck of traditional materials in high-fluoride systems and has wide applicability and high efficiency in uranium extraction.

CN123041602APending Publication Date: 2026-11-06NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611204530.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing technologies struggle to efficiently and selectively separate uranyl ions in environments with high fluoride ion concentrations. Traditional adsorption materials exhibit poor selectivity in high-fluoride systems and cannot effectively handle interference from high-concentration fluoride ions.

Method used

Sulfonic acid functionalization was performed on Magnéli phase Ti4O7 material. By introducing sulfonic acid groups on the surface of Ti4O7, sulfonic acid functionalized Ti4O7 material was formed for electrochemical uranium extraction. Combining its high conductivity and chemical stability, selective enrichment of uranium ions was achieved.

Benefits of technology

It maintains the preferential coordination and enrichment ability of uranyl ions under high fluoride ion concentration, which improves uranium extraction efficiency. It has high electrochemical uranium extraction efficiency and a wide pH range, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the fields of new materials and uranium extraction from high-fluoride wastewater, specifically to a sulfonic acid-functionalized Ti4O7 material, its preparation method, and its application in uranium extraction from high-fluoride wastewater. By introducing sulfonic acid groups onto Ti4O7 for chemical modification, the sulfonic acid groups are uniformly and stably bonded to Ti4O7. The resulting sulfonic acid-functionalized composite material can efficiently and selectively adsorb and electrocatalytically reduce uranium ions in high-fluoride uranium-containing wastewater under electrochemical action. It exhibits high uranium extraction capacity and significant resistance to fluoride ion interference, providing a new approach and option for uranium extraction from high-fluoride wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nuclear engineering and new materials technology, specifically relating to a sulfonic acid-functionalized Ti4O7 material and its preparation method, as well as the application of this material in the electrochemical uranium extraction from uranium-containing wastewater under high-concentration fluoride ion interference environment. Background Technology

[0002] With the rapid development of the global nuclear energy industry, uranium, as a core resource in the nuclear fuel cycle, has become increasingly strategically important. However, uranium mining, nuclear fuel processing, and nuclear power plant operation generate large amounts of uranium-containing radioactive wastewater. Improper treatment not only wastes uranium resources but also poses a serious threat to the ecological environment and human health. Therefore, developing efficient and economical uranium-containing wastewater treatment technologies to achieve the dual goals of uranium resource recovery and environmental protection has become an important research direction in the nuclear fuel cycle field. During the production of nuclear fuel elements, gaseous UF6 undergoes a gas-phase hydrolysis reaction with water vapor, producing a large amount of uranium-containing hydrofluoric acid solution after condensation. A significant characteristic of this type of wastewater is the presence of high concentrations of fluoride ions (HF concentrations can reach 10%–40%) and a certain concentration of uranyl ions. Conventional uranium-containing wastewater treatment methods include ion exchange, chemical precipitation, solvent extraction, and membrane separation. However, the strong corrosiveness of hydrofluoric acid places extremely high demands on treatment technologies and equipment materials, limiting the practical application of traditional methods. Crucially, the large amount of fluoride present in the wastewater... - Will with UO2 2+ Strong coordination occurs, forming a stable, water-soluble [UO2Fn] compound. 2-n (n=0-4) Complexes. This coordination effect significantly reduces the selective adsorption capacity of traditional adsorbent materials for uranyl, becoming a core bottleneck restricting the treatment efficiency of high-fluoride uranium-containing wastewater. How to achieve efficient and selective separation of uranium under harsh conditions of high fluoride ion concentration is a technical challenge that urgently needs to be overcome.

[0003] Magnéli phase titanium suboxide (Ti n O 2n-1 Ti4O7 is a class of non-stoichiometric titanium oxides, among which Ti4O7 is the phase with the best electrical conductivity, with a theoretical conductivity as high as 1995 S·cm. -1 Its electrical conductivity is higher than that of graphite (727 S·cm). -1Ti4O7 is typically prepared by the reduction of TiO2 in a high-temperature H2 atmosphere, a process accompanied by the formation of oxygen vacancies. This material possesses excellent electrical conductivity, outstanding chemical stability, and corrosion resistance. Studies have shown that Ti4O7 has an expected half-life of 50 years in 1.0 M sulfuric acid at room temperature. These properties make it promising for applications in electrocatalytic oxidation degradation of organic pollutants and electrochemical water treatment. However, the limited number of surface active sites in pristine Ti4O7 restricts its direct application in the extraction and treatment of uranium-containing wastewater due to insufficient adsorption capacity for target metal ions. Sulfonic acid groups (-SO3H), on the other hand, are typical strong acidic functional groups with excellent hydrophilicity, ion exchange capacity, and metal ion coordination ability. Numerous studies have shown that sulfonic acid groups can increase the negative charge density on the material surface, enhance the interfacial interaction between the material and metal ions, and improve the wettability and mass transfer efficiency of the material in aqueous solutions. Furthermore, sulfonic acid groups can also enhance the enrichment capacity of target ions by forming stable coordination with the metal center through oxygen atoms. However, existing research on sulfonic acid functionalized materials has mostly focused on carbon-based, silicon-based, or polymer matrix, and there are no reports of combining sulfonic acid functionalization with Magnéli phase conductive titanium oxide (Ti4O7) for electrochemical uranium extraction.

[0004] Based on the above, combining Magnéli phase titanium suboxide with sulfonic acid groups to develop sulfonic acid-functionalized Ti4O7 materials that combine conductivity, chemical stability, and uranium selectivity has significant application value. Summary of the Invention

[0005] The purpose of this invention is to combine the excellent electrical conductivity and corrosion resistance of Ti4O7 with the excellent coordination ability of sulfonic acid groups to develop a sulfonic acid-functionalized Ti4O7 material, and to provide its preparation method and applications. The aim is to provide a novel functional material with both selectivity and stability for the efficient treatment of high-fluoride uranium-containing wastewater.

[0006] To achieve the aforementioned objective, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing sulfonic acid-functionalized Ti4O7 materials, comprising the following steps:

[0008] (1) Preparation of Ti4O7: Anatase titanium dioxide powder was placed in a tube furnace and a mixed gas flow containing hydrogen and inert gas was introduced at a temperature of 900℃~1100℃ for 1~8 h to reduce it to obtain titanium heptoxide powder.

[0009] (2) Preparation of sulfonic acid functionalized Ti4O7: The Ti4O7 obtained in step (1) is dispersed in an aprotic organic solvent, and sulfonic acid lactone compounds are added. The mixture is refluxed and stirred at 80℃~130℃ for 24~72 h. After the reaction is completed, the mixture is precipitated with deionized water, filtered and separated, and dried under vacuum to obtain sulfonic acid functionalized Ti4O7 material.

[0010] As a further improvement of the present invention, in step (1), the temperature of the tubular furnace is set at 950℃~1050℃, the mixed gas is 5% hydrogen and 95% argon by volume, and the reduction time is 2~5 h.

[0011] As a further improvement of the present invention, the sulfonyl lactone compound in step (2) is at least one of 1,3-propanesulfonyl lactone, 1,2-ethanesulfonyl lactone or 1,4-butanesulfonyl lactone; and the aprotic organic solvent is at least one of toluene, xylene or tetrahydrofuran.

[0012] As a further improvement of the present invention, in step (2), the molar ratio of Ti4O7 to sulfonyl lactone is 1:3.5 to 5.0, and the amount ratio of Ti4O7 to aprotic organic solvent is 1 g:(40 to 80 mL).

[0013] As a further improvement of the present invention, in step (2), the sulfonyl lactone compound is 1,3-propanesulfonyl lactone, the aprotic organic solvent is toluene, the molar volume ratio of Ti4O7, 1,3-propanesulfonyl lactone and toluene is 1:5:60mL; the reflux temperature is 100℃~110℃, the reaction time is 36~48 h, and the stirring speed is 260~320 r / min.

[0014] As a further improvement of the present invention, in step (2), the filtered and separated material is vacuum dried at 60℃~80℃ for 8~10 h.

[0015] Secondly, the present invention provides a sulfonic acid-functionalized Ti4O7 material, which uses Ti4O7 as a conductive framework, and sulfonic acid alkyl chain functional groups are covalently bonded to the surface of Ti4O7, wherein the sulfonic acid alkyl chain structure is —(CH2). n —SO3H, where n is an integer from 2 to 4; in the infrared spectrum 1020–1050 cm⁻¹ -1 and 1110~1140 cm -1 The peaks at the points exhibit characteristic peaks of symmetrical and asymmetrical stretching vibrations at S=O, respectively.

[0016] Thirdly, the present invention provides sulfonic acid-functionalized Ti4O7 materials prepared by the method described in the first aspect.

[0017] Fourthly, this invention provides the application of the above-mentioned sulfonic acid-functionalized Ti4O7 material in uranium extraction from high-fluoride wastewater.

[0018] As a further improvement of the present invention, the application includes the following steps: a working electrode is prepared by loading sulfonic acid-functionalized Ti4O7 material onto a conductive substrate, an inert metal electrode is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode electrochemical system; the working electrode is placed in uranium-fluorine-containing wastewater, and a negative potential of -0.3 V to -2.0 V is applied to electrochemically reduce, enrich, and extract uranium ion in the wastewater.

[0019] The beneficial effects of adopting the above technical solution are as follows:

[0020] 1. This invention selects Magnéli phase Ti4O7 as the support substrate, utilizing its high conductivity to enable the material to not only perform adsorption and enrichment in the electrochemical system, but also directly participate in the electrochemical reduction process as a working electrode, realizing a dual synergistic uranium extraction mechanism of adsorption and reduction; sulfonyl lactone compounds are used to chemically modify the hydroxyl groups on the surface of Ti4O7, and the sulfonyl groups are in high F - It remains in a protonated state in a highly acidic environment and does not participate in F. - The competitive coordination allows it to maintain preferential coordination and enrichment of uranyl ions even under high fluorine interference conditions, overcoming the core bottleneck of poor selectivity of traditional adsorption materials in high fluorine systems.

[0021] 2. The sulfonic acid-functionalized Ti4O7 material provided by this invention has been experimentally verified to have good high fluorine anti-interference performance, high electrochemical uranium extraction efficiency, and low interference from coexisting ions. It also has a wide pH range, a wide range of applications, a wide range of raw material sources, and a simple preparation process, making it suitable for large-scale production. Attached Figure Description

[0022] Figure 1 Scanning electron microscope images of Ti4O7-SO3H prepared in Example 2 and in Example 1 of the present invention;

[0023] Figure 2 The X-ray diffraction patterns of Ti4O7-SO3H prepared in Example 2 and that in Example 1 are shown below.

[0024] Figure 3 The nitrogen adsorption-desorption isotherms of Ti4O7-SO3H prepared in Example 2 of this invention and that of Example 1 are shown.

[0025] Figure 4 Fourier transform infrared spectra of Ti4O7-SO3H prepared in Example 2 of this invention and that in Example 1;

[0026] Figure 5The results of uranium extraction tests under different voltages using the Ti4O7-SO3H material in Example 4 of this invention are shown.

[0027] Figure 6 The results of the uranium extraction performance test of Ti4O7-SO3H material in high-fluoride wastewater in Example 5 of this invention are shown.

[0028] Figure 7 The results of the experiment on the influence of coexisting ions on the Ti4O7-SO3H material in Example 6 of this invention;

[0029] Figure 8 The results of uranium extraction performance tests of Ti4O7-SO3H material at different pH values ​​in Example 7 of this invention are shown. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described clearly and completely below in conjunction with specific embodiments.

[0031] Example 1: Preparation of Ti4O7 material

[0032] 1 g of anatase titanium dioxide powder was placed in a tube furnace, and the temperature was increased at a rate of 5 °C / min. -1 At 1030℃, under a mixed gas flow of 5% hydrogen and 95% argon, with a gas flow rate of 100 sccm, and after holding at this temperature for 5 h, titanium dioxide powder was reduced to dark blue Ti4O7 powder.

[0033] Example 2: Preparation of Ti4O7-SO3H composite material

[0034] One g of Ti4O7 material prepared according to the method of Example 1 was dispersed in a double-necked round-bottom flask containing 60 ml of toluene. Two g of 1,3-propanesulfonate lactone was added under stirring at a rotation speed of 300 r / min, and the mixture was refluxed at 110 °C for 48 h. After precipitation and washing with deionized water, filtration, and vacuum drying at 80 °C, Ti4O7-SO3H powder was obtained.

[0035] Example 3: SEM, XRD, BET, and FT-IR structural characterization

[0036] Electron microscopy was performed on Ti4O7 obtained in Example 1 and Ti4O7-SO3H obtained in Example 2. The results are as follows: Figure 1 As shown, Ti4O7-SO3H exhibits a similar surface morphology to Ti4O7, but scanning electron microscopy reveals that Ti4O7 exhibits an aggregated granular structure, while the sulfonic acid-functionalized material displays a more porous structure.

[0037] X-ray diffraction patterns of Ti4O7 obtained in Example 1 and Ti4O7-SO3H obtained in Example 2 are shown below. Figure 2 As shown, Ti4O7 and Ti4O7-SO3H exhibit the same characteristic diffraction peaks, indicating that sulfonic acid-functionalized Ti4O7 completely retains its crystal structure.

[0038] Nitrogen adsorption-desorption isotherms were used to characterize Ti4O7 obtained in Example 1 and Ti4O7-SO3H obtained in Example 2. The spectra are shown below. Figure 3 As shown, for Ti4O7, after sulfonic acid functionalization, chemical reactions may occur on the surface or near the surface, causing the originally dense or agglomerated particle structure to become loose, opening up the originally closed surface, thereby increasing the specific surface area available for physical adsorption as a whole.

[0039] Fourier transform infrared spectroscopy was performed on Ti4O7 obtained in Example 1 and Ti4O7-SO3H obtained in Example 2. The spectra are shown below. Figure 4 As shown, infrared spectroscopy analysis at 3430 cm⁻¹... -1 and 1629 cm -1 They exhibit typical OH stretching and bending vibration peaks, and at 1034 cm⁻¹ -1 and 1126 cm -1 Characteristic peaks of S=O symmetric and asymmetric stretching vibrations of sulfonic acid groups were found at the site.

[0040] Example 4: Uranium Extraction Tests at Different Voltages

[0041] The Ti4O7-SO3H obtained in Example 2 was subjected to uranium extraction tests at different voltages. The uranium extraction efficiency at different voltages was investigated using an electrochemical workstation and a three-electrode system. The specific methods and steps are as follows:

[0042] Weigh 5 mg of the Ti4O7-SO3H material obtained in Example 2, add 1 ml of ethanol and 50 μL of 5 wt% Nafion, sonicate for 30 min, and then drop the mixture onto 2×3 cm carbon paper. Dry the paper at 100℃ to obtain an electrode sheet. Use the Ti4O7-SO3H-loaded electrode sheet as the working electrode in a three-electrode system, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. Place a rotor in the reaction cell, rotating at 300-400 r / min. Add 100 mL of fluorinated uranyl solution to the electrolytic cell, with KF providing fluoride ions and F... -With a concentration of 1 g / L, an initial U(VI) concentration of 30 ppm, and a system pH of 6.2, voltages of -0.3 V, -0.5 V, -0.8 V, -1 V, -1.5 V, and -2 V were applied. The supernatant was collected by filtration through a 0.22 μm filter at different time points, and the absorbance was measured using the arsene III method. The removal rate of uranyl ions by the material was calculated based on the initial concentration and the measured residual concentration.

[0043] The results are as follows Figure 5 As shown, Ti4O7-SO3H exhibits extremely high removal capacity under electrochemical conditions, with removal efficiency approaching 100% at -1.5 V and -2 V conditions for 600 min.

[0044] Example 5: Performance Test of Uranium Extraction from High-Fluoride Wastewater Using Ti4O7-SO3H Material

[0045] Do F respectively - Five groups of different F solutions with concentrations of 2, 5, 10, 15, and 20 g / L and a total solution volume of 30 ppm were prepared, with a total volume of 100 mL. - Electrochemical uranium extraction tests at different concentrations were conducted. Electrode sheets were prepared in the same manner as in Example 4. A voltage of -1.5V was applied, and the supernatant was collected by filtration through a 0.22 μm filter at different time points. The absorbance was measured using the arsene III method. The removal rate of uranyl ions by the material was calculated based on the initial concentration and the measured residual concentration.

[0046] The results are as follows Figure 6 As shown, Ti4O7-SO3H in F - Within the concentration range of 2–20 g / L, the uranium removal rate of Ti4O7-SO3H material decreased relatively little, and in the F - It can maintain effective uranium extraction capacity even under harsh conditions of 20 g / L concentration, which is significantly better than traditional adsorbent materials.

[0047] Example 6: Test on the influence of coexisting ions on Ti4O7-SO3H materials

[0048] F - The concentration was 1 g / L, and the U concentration was 30 ppm. Eight groups were formed, each with 30 ppm of background ion solution (CO3). 2- SO4 2- Cl - C2O4 2- NO3 - Na + K + NH 4+The total solution volume was maintained at 100 ml. Electrode sheets were prepared in the same manner as in Example 4. A voltage of -1.5 V was applied, and the supernatant was collected by filtration through a 0.22 μm filter at different time points. The absorbance was measured using the arsene III method. The removal rate of uranyl ions by the material was calculated based on the initial concentration and the measured residual concentration.

[0049] The results are as follows Figure 7 As shown, in CO3 2- SO4 2- Cl - C2O4 2- NO3 - Na + K + NH 4+ Even in the presence of common coexisting ions, the uranium extraction performance of the material does not decrease significantly, and the selectivity is excellent.

[0050] Example 7: Uranium extraction performance test of Ti4O7-SO3H material at different pH levels

[0051] F - The concentration was 1 g / L, the U concentration was 30 ppm, and the total solution volume was 100 mL. The pH of the mixed solution was adjusted to 1.0, 3.0, 5.0, 7.0, 9.0, and 11.0 with 2 M H₂SO₄ and 3 M NaOH, respectively. Electrode sheets were prepared in the same manner as in Example 4. A voltage of -1.5 V was applied, and the supernatant was collected by filtration through a 0.22 μm filter at different time points. The absorbance was measured using the arsene III method. The removal rate of uranyl ions by the material was calculated based on the initial concentration and the measured residual concentration.

[0052] The results are as follows Figure 8 As shown, Ti4O7-SO3H material has uranium extraction capability in the pH range of 1.0 to 11.0, with the best performance at pH 5.0, making it suitable for various practical wastewater treatment scenarios.

[0053] Example 8: Boundary Parameter Example, Low Temperature / Short Time Preparation

[0054] 1 g of anatase titanium dioxide powder was placed in a tube furnace and kept at 950 °C for 2 h under a mixed gas flow of 5% hydrogen and 95% argon to obtain Ti4O7 powder.

[0055] 1 g of the above Ti4O7 material was dispersed in 40 mL of toluene, and 1.4 g of 1,3-propanesulfonate lactone was added. The mixture was stirred at 260 r / min and refluxed at 100 °C for 36 h. After precipitation with deionized water, the mixture was filtered and dried under vacuum at 60 °C for 10 h to obtain Ti4O7-SO3H powder.

[0056] The obtained product was characterized by infrared radiation, confirming a depth of 1034 cm⁻¹. -1 and 1126 cm -1 The characteristic peak of sulfonic acid group was present; the uranium extraction performance was determined according to the method of Example 4, and the results showed that the uranium removal rate of the sample reached 100% under the conditions of -1.5 V and 600 min.

[0057] Comparative Example 1: Uranium Extraction Test of Unfunctionalized Ti4O7

[0058] Take 5 mg of Ti4O7 prepared in Example 1 and prepare an electrode sheet in the same manner as in Example 4. In 100 mL of solution containing 30 ppm uranyl ions and F... - Electrochemical uranium extraction was performed in a 1 g / L solution by applying a voltage of -1.5 V, and the residual concentration of uranyl ions at different time points was recorded.

[0059] The results show that the uranium removal rate of unfunctionalized Ti4O7 within 600 min under the same conditions is about 75%, which is significantly lower than the nearly 100% removal rate of Ti4O7-SO3H, proving that sulfonic acid functionalization improves uranium extraction performance.

[0060] Comparative Example 2

[0061] 1.0 g of Ti4O7 prepared according to the method of Example 1 was weighed and placed in an Erlenmeyer flask. Then, 50 mL of 2 M H2SO4 was added to the Erlenmeyer flask, and the mixture was stirred for 6 h. The material was then collected by filtration, and the filtered material was dried in an oven at 80 °C to obtain hydroxyl-functionalized Ti4O7. Electrode sheets were prepared in the same manner as in Example 4. The mixture was heated in 100 mL of a solution containing 30 ppm uranyl ions and F... - Electrochemical uranium extraction was performed in a 1 g / L solution by applying a voltage of -1.5 V, and the residual concentration of uranyl ions at different time points was recorded.

[0062] The results showed that hydroxylated Ti4O7 achieved a uranium removal rate of approximately 77% within 600 min under the same conditions, significantly lower than the nearly 100% removal rate of Ti4O7-SO3H, demonstrating that sulfonic acid groups have a significant effect on uranium removal under high F2+ conditions. - The selective advantage of anti-interference under the interference system.

[0063] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing sulfonic acid-functionalized Ti4O7, characterized in that, Includes the following steps: (1) Preparation of Ti4O7: Anatase titanium dioxide powder was placed in a tube furnace and a mixed gas flow containing hydrogen and inert gas was introduced at a temperature of 900℃~1100℃ for 1~8 h to reduce it and obtain titanium heptoxide powder. (2) Preparation of sulfonic acid functionalized Ti4O7: The Ti4O7 obtained in step (1) is dispersed in an aprotic organic solvent, and sulfonic acid lactone compounds are added. The mixture is refluxed and stirred at 80℃~130℃ for 24~72 h. After the reaction is completed, the mixture is precipitated with deionized water, filtered and separated, and dried under vacuum to obtain sulfonic acid functionalized Ti4O7 material.

2. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the tubular furnace is set at 950℃~1050℃, and the heating rate is 1~5℃min. -1 The mixed gas consists of 5% hydrogen and 95% argon by volume, with a gas flow rate of 25-250 sccm and a reduction time of 2-5 h.

3. The preparation method according to claim 1, characterized in that, In step (2), the sulfonyl lactone compound is at least one of 1,3-propanesulfonyl lactone, 1,2-ethanesulfonyl lactone, or 1,4-butanesulfonyl lactone; and the aprotic organic solvent is at least one of toluene, xylene, or tetrahydrofuran.

4. The preparation method according to claim 1 or 3, characterized in that, In step (2), the molar ratio of Ti4O7 to sulfonyl lactone compounds is 1:3.5 to 5.0, and the molar ratio of Ti4O7 to aprotic organic solvent is 1 g:40 to 80 mL.

5. The preparation method according to claim 1, characterized in that, In step (2), the sulfonyl lactone compound is 1,3-propanesulfonyl lactone, the aprotic organic solvent is toluene, and the molar volume ratio of Ti4O7, 1,3-propanesulfonyl lactone and toluene is 1:5:60 mL; the reflux temperature is 100℃~110℃, the reaction time is 36~48 h, and the stirring speed is 260~320 r / min.

6. The preparation method according to claim 1, characterized in that, After filtration and separation in step (2), the product is vacuum dried at 60℃~80℃ for 8~10 h.

7. A sulfonic acid-functionalized Ti4O7 material, characterized in that: Using Ti4O7 as the conductive framework, the surface of Ti4O7 is covalently connected with sulfonic acid alkyl chain functional groups, the structure of which is —(CH2). n —SO3H, where n is an integer from 2 to 4; in the infrared spectrum 1020–1050 cm⁻¹ -1 and 1110~1140 cm -1 The peaks at the points exhibit characteristic peaks of symmetrical and asymmetrical stretching vibrations at S=O, respectively.

8. A sulfonic acid-functionalized Ti4O7 material prepared by the method according to any one of claims 1 to 6.

9. The application of the sulfonic acid-functionalized Ti4O7 material according to claim 7 or 8 in uranium extraction from high-fluoride wastewater.

10. The application according to claim 9, characterized in that, The application includes the following steps: a working electrode is prepared by loading sulfonic acid-functionalized Ti4O7 material onto a conductive substrate, using an inert metal electrode as the counter electrode and Ag / AgCl as the reference electrode to form a three-electrode electrochemical system; the working electrode is placed in uranium-fluorine-containing wastewater, and a negative potential of -0.3 V to -2.0 V is applied to electrochemically reduce, enrich, and extract uranium ion in the wastewater.